Indications for caesarean sections at ≥34 weeks among nulliparous women and differential composite maternal and neonatal morbidity. (10th February 2014) - Chauhan, SP; Beydoun, H; Hammad, IA; Babbar, S; Hill, JB; Mlynarczyk, M; D'Alton, ME; Abuhamad, AZ; Vintzileos, AM; Ananth, CV
Abstract : Objective: To compare composite maternal and neonatal morbidities (CMM, CNM) among nulliparous women with primary indications for caesarean section (CS) as acute clinical emergency (group I; ACE), non‐reassuring fetal heart rate (group II) and arrest disorder (group III). Design: A multicentre prospective study. Setting: Nineteen academic centres in the USA, with deliveries in 1999–2002. Population: Nulliparous women ( n =  9829) that had CS. Methods: Nulliparous women undergoing CS for three categories of indications were compared using logistic regression model, adjusted for five variables. Main outcome measures: CMM was defined as the presence of any of the following: intrapartum or postpartum transfusion, uterine rupture, hysterectomy, cystotomy, ureteral or bowel injury or death; CNM was defined as the presence of any of the following: umbilical arterial pH <7.00, neonatal seizure, cardiac, hepatic, renal dysfunction, hypoxic ischaemic encephalopathy or neonatal death. Results: The primary reasons for CS were ACE in 1% (group I, n =  114) non‐reassuring FHR in 29% (group II; n =  2822) and failed induction/dystocia in the remaining 70% (group III; n =  6893). The overall risks of CMM and CNM were 2.5% (95% confidence intervals, CI, 2.2–2.8%) and 1.9% (95% CI 1.7–2.2), respectively. The risk of CMM was higher in group I than in group II (RR 4.1, 95% CI 3.1, 5.3), and group III (RR 3.2, 95% CI 2.7, 3.7). The risk of CNM was also higher in group I than in group II (RR 2.8, 95% CI 2.3, 3.4) and group III (RR 14.1, 95% CI 10.7, 18.7). Conclusions: Nulliparous women who have acute clinically emergent caesarean sections are at the highest risks of both composite maternal and neonatal morbidity and mortality.